Teacher learning and student outcomes in the context of classroom discourse. Findings from a video-based teacher professional development programme - Katharina Kiemer; Alexander Gröschner; Ann-Kathrin Pehmer; Tina Seidel (Firenze University Press, 2014)
We present an innovative teacher professional development programme (TPD) focusing on the re-definition of teachers' discourse behaviour. We report findings on teacher learning and student outcomes, and reflect on practical implications and directions for future research on the programme. In the "Dialogic Video Cycle" (DVC) six teachers participated in a year-long intervention built on effective components of TPD and using videos of teachers' own practices as tools for reflection and basis for group discussions. We compared the DVC with a traditional TPD programme (n= 4 teachers). Additionally, students (N= 226) were assessed regarding their motivational orientations and individual beliefs. Results show that effective TPD components could successfully be implemented in the DVC and that this new and innovative programme enhances teachers' performance in classroom discourse and affects students' interest in the subject, self-efficacy and domain-specific self-concept of ability positively. Thus, the DVC seems a promising tool to foster teacher learning with an impact on perceived student motivation and learning.   Presentiamo un programma innovativo per lo sviluppo professionale degli insegnanti (TPD), centrato sulla ridefinizione della conduzione di interazioni verbali in classe. Sono riportati i risultati dell'apprendimento di insegnanti e studenti, e la riflessione sulle implicazioni pratiche per la ricerca futura sul programma. Nel "Dialogic Video Cycle" (DVC) sei insegnanti hanno partecipato per un anno a un intervento di TPD mediante videoregistrazioni usate come strumenti di riflessione sulle proprie pratiche e per le discussioni di gruppo. Abbiamo confrontato il DVC con un programma TPD tradizionale (n= 4 insegnanti). Inoltre sono stati valutati gli orientamenti degli studenti (N= 226) in termini di motivazione e fiducia nelle proprie capacità. I risultati mostrano che le componenti efficaci del TPD potrebbero essere attuate con successo nel DVC e che questo programma migliora le prestazioni degli insegnanti nella conduzione del discorso in aula e stimola negli studenti l'interesse per l'argomento, il senso di auto-efficacia e il concetto di sé. Il DVC sembra uno strumento promettente per favorire l'apprendimento degli insegnanti con un impatto sulla motivazione e sull'apprendimento degli studenti.